Effectiveness of the San Yai Rak 3-in-1 lingerie Innovation in Reducing Breast Engorgement, Back Pain, and Afterpain in Postpartum Mothers - Siriphan, Siriphan; Chantaburee, Narisa; Yodkaew, Urai; Ieamwuthiwattana, Juthamas (Princess of Naradhiwas University Journal, 2025)
Background and Objectives Normal labor postpartum mothers at Narathiwat Rajanagarindra Hospital experience breast engorgement, back pain, and afterpain, and they desire relief from these symptoms. Therefore, the researcher implemented the San Yai Rak 3-in-1 lingerie innovation in this study. This research was a quasi-experimental study measuring before and after the use of the San Yai Rak 3-in-1 lingerie innovation. The objectives were to: 1) study breast engorgement, back pain, and afterpain in postpartum mothers; 2) compare breast engorgement, back pain, and afterpain in postpartum mothers before and after using the San Yai Rak 3-in-1 lingerie innovation; and 3) study satisfaction with the use of the San Yai Rak 3-in-1 lingerie innovation. Methods The sample group consisted of 60 postpartum mothers. Data was collected using a personal information questionnaire, a breast engorgement questionnaire, a back pain questionnaire, an afterpain questionnaire, and a satisfaction assessment questionnaire for the use of the San Yai Rak 3-in-1 lingerie innovation for breast engorgement, back pain, and afterpain. The Cronbach’s alpha coefficient reliabilities of the breast engorgement, back pain, and afterpain questionnaires and the satisfaction assessment questionnaire for the use of the San Yai Rak 3-in-1 lingerie innovation were 0.91 and 0.86, respectively. Data were analyzed using descriptive statistics and the paired t-test. Results The research findings indicated that postpartum mothers before using the San Yai Rak 3-in-1 lingerie innovation had a mild degree of breast engorgement symptoms (45%) and a moderate degree (45%). They reported mild back pain (95%). They reported mild afterpain (45%) and a moderate degree of afterpain (45%). Postpartum mothers after using the San Yai Rak 3-in-1 lingerie innovation had significantly lower average scores for breast engorgement, back pain, and afterpain compared to before using the lingerie innovation, with statistical significance at the .05 level (t = 2.15, 2.65, 2.85, p < .05). The satisfaction of postpartum mothers after using the San Yai Rak 3-in-1 lingerie innovation to reduce breast engorgement, back pain, and afterpain was at a high level (M = 2.65, S.D. = 0.36). Conclusion and Recommendations The San Yai Rak 3-in-1 lingerie innovation can be used to reduce breast engorgement, back pain, and afterpain in mothers after normal childbirth. This provides drug-free pain relief, and in future research, this innovation can be adapted by replacing the gel with local herbs from the three southern border provinces that have properties to relieve breast engorgement, back pain, and afterpain.